Conditions and procedures for the establishment of political parties in Iraqi law - طالب, مصدق عادل; بلاسم, حسام عبد الحسين (Journal of Legal Sciences, 2021)
The establishment of political parties in Iraqi law is subject to several conditions, including the conditions related to the principles and objectives of the parties and the conditions related to membership in the parties, as well as the establishment of a number of procedures. These conditions and procedures are governed by the Political Parties Law No. (36) of the year 2015, And another represents a restriction on the freedom to establish political parties and graduated from the framework of the organization authorized by the ordinary legislator under the constitutional assignment under the text of Article (39) of the Constitution to restrict and confiscation of the freedom to establish political parties, and we have finished through the search to a group of recommendations In order to deal with these texts, which have some shortcomings.